2017
DOI: 10.1177/1010428317697563
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and gene polymorphism are two independent events in regulation of GSTP1 gene expression

Abstract: Breast carcinogenesis is a multistep process, involving both genetic and epigenetic modification process of genes, involved in diverse pathways ranging from DNA repair to metabolic processes. This study was undertaken to assess the role of promoter methylation of GSTP1 gene, a member of glutathione-S-transferase family of enzymes, in relation to its expression, polymorphism, and clinicopathological parameters. Tissue samples were taken from breast cancer patients and paired with their normal adjacent tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
6
3
0
Order By: Relevance
“…In accordance with our study, Wu et al, (2016) and Bhat et al, ( 2017) found that significantly high frequency of the promotor methylation of GSTP1 gene in breast cancer cases (p ≤ 0.001) when compared to the promotor hypermethylation profile of the normal tissues, and significantly hypermethylation of GSTP1 promotor region in breast cancer (BC) as compared with Begnin Breast Disease (BBD) and controls ( p=0.010. Similar findings were reported by Fang et al, (2015) meta-analysis.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In accordance with our study, Wu et al, (2016) and Bhat et al, ( 2017) found that significantly high frequency of the promotor methylation of GSTP1 gene in breast cancer cases (p ≤ 0.001) when compared to the promotor hypermethylation profile of the normal tissues, and significantly hypermethylation of GSTP1 promotor region in breast cancer (BC) as compared with Begnin Breast Disease (BBD) and controls ( p=0.010. Similar findings were reported by Fang et al, (2015) meta-analysis.…”
Section: Discussionsupporting
confidence: 89%
“…They suggested that breast cancer patients with GSTP1 promotor hypermethylation may have a phenotype with more biological aggressiveness. The same observation was reported by Saxena et al, (2012) and Bhat et al, (2017) who showed significantly higher quantitative methylation levels in late stage compared to the early stage breast carcinoma (p = 0.014, p= 0.03; respectively). In addition Klajic et al, (2013) reported significant differences in methylation levels between the DCIS (Ductal carcinoma in situ) and invasive stage II tumors.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations